Introduction - Taves Sheffield, Rebecka; Giguère, Nicholas (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2019)
In their introduction to a special issue of the Papers of the Bibliographical Society of Canada, co-editors Rebecka Taves Sheffield and Nicholas Giguère provide a brief historical overview of the emergence of an LGBTQ+ press in Canada, and describe how the history of LGBTQ+ print culture in Canada is inextricably intertwined with the country’s history of media censorship, which has been often used to exclude LGBTQ+ people from public spaces. Sheffield and Giguère then summarize the articles, note, and review essay included in the special journal issue and describe how, on a whole, the contributors’ research sheds new light on the relationship between LGBTQ+ print media and the communities that it has both served and helped to create, despite persistent censorship.